Learning Express Library: An Evaluation. - Lindsay, J. Michael (Journal of Electronic Resources in Medical Libraries)
Learning Express Library, recently acquired by EBSCO Information Services, is a broad-based skill and test preparation tool designed to connect users with learning opportunities that would be of value to learners ranging from elementary school students to adults preparing for advanced degrees. This profile, while focusing on the relevance of this resource to health sciences libraries, will cover the content, including breadth of coverage and navigation, and subscription information for this resource.